Study on the Fault Diagnosis of Variable Speed Gearbox based on Improved Order Analysis and Adaptive VMD - Gang Feng; Tongtong Liu; Lingli Cui (Jixie chuandong)
Due to the complex operating conditions of the gearbox with variable speed， the frequency of the gearbox is unstable， the weak fault signal of the gear box may be hidden in the strong noise， it is not possible to directly apply the traditional time-frequency analysis method， which increases the difficulty of fault feature extraction. For the processing of the variable speed signal， the traditional calculation order analysis （COT） can solve the problem that the fault features of the variable speed gearbox are difficult to be extracted. However， because the resampling method used in the traditional COT is based on spline interpolation method， the frequency cannot be selected according to the frequency， resulting in uneven resampling interval. An improved order analysis is proposed， which resamples according to the angular velocity of each sampling point in order to improve the accuracy of order analysis， the accuracy of the order analysis is improved. At the same time， the noise of variable speed gearbox is more serious because of the complexity of power transmission. The variational mode decomposition （VMD） is often used to eliminate complex signal noise and extract weak fault signals hidden in strong noise. An adaptive VMD using energy method is proposed to determine the number of decomposition layers and then select the components for indexing， so that the effect of denoising is further improved. Through the analysis of the experimental signals， the method is used to verify the results. The results show that the method can effectively transform the signal of the gearbox with variable speed into the signal of order and identify the fault.